2021
DOI: 10.3390/catal11060684
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nickel(II) Homogeneous and Supported Complexes for the Hydrogenation of Furfural to Furfuryl Alcohol

Abstract: Nickel(II) complexes have been synthesized and characterized using nuclear magnetic resonance (NMR), infrared spectroscopy, high resolution mass spectroscopy, and elemental analysis. The complexes were evaluated as pre-catalysts in the direct hydrogenation of furfural to furfuryl alcohol. The pre-catalysts C1 and C4 gave higher furfural conversion (97% and 96%, respectively), as a result, they were also evaluated in the transfer hydrogenation of furfural using formic acid as the hydrogen source where higher fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…To confirm the homogeneity of the catalyst, alkylation reaction was conducted in the presence of 3.0 equiv. of Hg(0), however, does not affect the yield of 3 (Scheme 5d and Scheme S10) [14] . Intermolecular competitive experiments showed that, alkylation reaction of primary alkyl alcohols are quite slow in compare to aryl alcohols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the homogeneity of the catalyst, alkylation reaction was conducted in the presence of 3.0 equiv. of Hg(0), however, does not affect the yield of 3 (Scheme 5d and Scheme S10) [14] . Intermolecular competitive experiments showed that, alkylation reaction of primary alkyl alcohols are quite slow in compare to aryl alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…of Hg(0), however, does not affect the yield of 3 (Scheme 5d and Scheme S10). [14] Intermolecular competitive experiments showed that, alkylation reaction of primary alkyl alcohols are quite slow in compare to aryl alcohols. When an equimolecular mixture of 2 q-d2 and 2 q were used with 1 a, only a trace amount of 19-d3 was detected (Scheme 5e and Scheme S11-12).…”
Section: Chemcatchemmentioning
confidence: 99%
“…6,9,10 To the best of our knowledge, very few reports are found in the literature on the application of homogenous Rh, Ni, Pd and Fe complexes as pre-catalysts in the hydrogenation of FF. [11][12][13][14] Lately, EL is mainly synthesised from various feedstocks such as LA and FA via catalytic reaction with ethanol. Some researchers have obtained EL from FA catalysed by sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic hydrogenation of FF has been widely investigated in the presence of transition and precious metal‐based catalysts 6,9,10 . To the best of our knowledge, very few reports are found in the literature on the application of homogenous Rh, Ni, Pd and Fe complexes as pre‐catalysts in the hydrogenation of FF 11–14 . Lately, EL is mainly synthesised from various feedstocks such as LA and FA via catalytic reaction with ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…Common hydrogen donors such as isopropanol, ethanol, methanol and formic acid are widely used with metal catalysts in TH, specifically, ruthenium, 33 iridium, 34 platinum, 35 palladium, 36 iron, 37 manganese 38 and nickel 39 homogeneous catalysts. The versatile tridentate architecture of pincer ligands has been identified as effective in altering and regulating metal complex characteristics across the periodic table.…”
Section: Introductionmentioning
confidence: 99%